THE PROFESSIONAL IMPROVEMENT OF THE CUBAN HEALTH SECTOR IN THE EDUCATIONAL CONTEXT OF THE XXI CENTURY - Villareño-Domínguez, Dunieski (2021)
The changes that in dissimilar orders are produced on a global scale, constitute today a reality to transform and impact in its very essence to the universities. Th e university educational context is the ideal space to watch over, clarify the nature and connotation of such changes and, consequently, take responsibility for the graduation of professionals with a coherent and creative attitude. Th e postgraduate program, as one of its substantive processes, deals with the continuous updating and reorientation of professionals, through a systemic conglomerate of proposals that prepares them for a better performance. Th e study intends to present theoretical and methodological assumptions related to the projection of professional improvement in the Cuban health sector and to encourage and caution about action consistent with these aspirations, besides recognizing opportunities and limiting factors that persist in their realization It is concluded that the Cuban medical university in the educational context of the 21st century, focuses on postgraduate activity, specifi cally professional improvement, based on a renewed and tempered mission to the socio-historical-concrete moment that is lived. Th e achievement of this aspiration is favored by state policies that demonstrate quality, equity and accessibility, prioritizing the training of professionals with the ability, performance, creativity and suitable values to face important challenges in the midst of economic, social, and health crisis, where limitations cannot in any way hinder the process of transformation and constant review that its improvement deserves.